Knowledge, Willingness to Pay and Beliefs for Seasonal Influenza Vaccination, A Cross-Sectional Study from Jordan - Al-Taani, Ghaith M.; Muflih, Suhaib; Alsharedeh, Rawan; Altaany, Zaid (Jordan Journal of Pharmaceutical Sciences, 2023)
Background: Seasonal influenza is a viral illness associated with significant morbidity and mortality. Objectives: This study aimed to assess preferences for utilizing the seasonal influenza vaccine. Methods: Based on a review of the literature and discussions among the research team, a 37-item survey was created, pretested, and completed by the lay public in Irbid city. The survey assessed knowledge, willingness-to-pay, and beliefs regarding the seasonal influenza vaccine. Participants' willingness-to-pay for the influenza vaccine was determined using contingent valuation with a payment card. Logistic regression analysis was employed to determine predictors associated with willingness-to-pay. Results: A total of 347 responses constituted the study sample. Respondents rated their knowledge about the influenza vaccine as good or excellent (62.5% of the total received responses). Approximately one-half (45.3%) of the respondents were willing to pay 5 JD for the influenza vaccine. It was found that standard of living, living location (city vs. village), and occupation (i.e., employment status) were independent predictors associated with higher willingness-to-pay for the influenza vaccine. Conclusion: The participants were willing to pay a price close to the market price, thus affording the vaccine. Such data can help healthcare decision-makers develop promotive policies to improve vaccine uptake.